Isothermal remanent magnetization (IRM) gradient of Palouse loess at site CLY-2, eastern Washington, USA - Nicholas E Bader; Elliot A Broze; Molly A Coates; McKenzie M Elliott; Gabriella E McGann; Sarah Strozyk; Russell F Burmester (PANGAEA, 2024)
These data are from samples gathered in 2016 from the CLY-2 site in eastern Washington, USA (Location: 46.3131, -118.4874, WGS84). The CLY-2 is a roadcut exposing a vertical face of the Palouse loess containing carbonate paleosol horizons and tephras. The samples were collected from a set of three stepped trenches into the roadcut about 10-20 m apart. Each trench was excavated to a depth of about a meter to expose a fresh surface; the final ~10 cm was excavated with non-ferrous digging tools. Other magnetic properties were measured at Western Washington University extquotesingles Pacific Northwest Paleomagnetism Laboratory. To make isothermal remanent magnetization (IRM) gradient acquisition curves, we loaded a subset of sample pots into gel capsules and measured the samples extquotesingle response to a magnetic field in a Princeton Micromag 3900 vibrating sample magnetometer, which provided fields up to 2.2 tesla. To detect the presence of high-coercivity components such as goethite, we subjected a subset of samples to higher fields (stepwise up to 5 tesla), using an ASC Scientific Model IM-10-30 Impulse Magnetizer, and measured the IRM in a liquid He-cooled, 3-axis superconducting magnetometer (2G Enterprises Model 755) with a sensitivity of 0.001 mA/m, in a field-free room, demagnetizing the sample between measurements.